A notícia como ela é: uma análise do discurso de manchetes online - Sales, Maria Angélica (2017)
This research has the objective of investigating the usage and recurrence of linguistic-discursive resources in the constitution of news headlines on an Internet portal. Based on the verbal language used on the digital platform, we have also analyzed how certain discursive modes utilized in the titles (such as the fact or speech reported, modalization, among others) intend to make the news story more attractive to the reader. As our corpus, we have selected 13 headlines from the News portal UOL published between August 27th, 2016, and September 3rd, 2016, period in which the impeachment of former president Dilma Rousseff occurred (31st of August), with the addition of the three days prior to event (from August 27th to 30th) and the three days after it (From September 1st to 3rd). The theoretical references of this dissertation are mainly situated in the field of Discourse Analysis, with emphasis on the principles of the enunciative clutch concept, direct and indirect discourse and detached enunciation proposed by Maingueneau (2013), supported on Bakhtin (2006). We have also resorted to the information staging strategies presented by Charaudeau (2010). We intend, with this research, to contribute not only to the studies on the peculiarities of the press online, but also to deepen the reflection of the market on how journalism is done. The results obtained demonstrate that there is a visible commitment to divulge relevant and/or exclusive content on the main event of the period studied (the impeachment), but there are situations when this commitment is broken by the usage of statements which prioritize the spectacle over the fact. Many linguistic and discursive choices used in the headlines are justifiable as attempts to mobilize the public interest. By such means, the Internet portal conducts a subtle staging of the information discourse, in which the journalist’s interpretation surpasses the actual news